Development of Teaching Materials In A Direct Current Electric Circuit Based on The Blended Learning Model Oriented High Order Thinking Skill (HOTS) - Desi Ramadhanti; Irfan Yusuf; Kaleb Amaghi Yenusi; Sri Wahyu Widyaningsih (Kasuari: Physics Education Journal (KPEJ), 2020)
Research on development of teaching materials, the purpose are know the validity, practicality, and effectiveness of teaching materials in a direct current electric circuit based on Blended Learning model oriented High Order Thinking Skill (HOTS). The development uses ADDIE model are analysis, design, development, implementation and evaluation. In this research, the validation and reliability using Content validity Index (CVI) equation and alpha formula. Results of instrument validity are the valid and reliable categories. The effectiveness and practicality analysis uses Rasch Model with Winstep application. The results of the effectiveness and practicality that all statements can agreed by students. From all of statements practicality and effectiveness, it can concluded the development of direct current electricity teaching materials based on the Blended Learning model can said to be valid, practical and effective to use.